A minireview on doped carbon dots for photocatalytic and electrocatalytic applications. Issue 26 (29th June 2020) - Zhang, Zhengting; Yi, Guiyun; Li, Peng; Zhang, Xiuxiu; Fan, Haiyang; Zhang, Yulong; Wang, Xiaodong; Zhang, Chuanxiang
Abstract : This minireview highlights recent advances on photocatalytic and electrocatalytic applications of doped CDs with improved electronic structures. Abstract : To date, carbon dots (CDs) or carbon quantum dots (CQDs), considered as alternatives to conventional fluorescent materials such as organic dyes and semiconductor quantum dots (QDs), have drawn significant attention from relevant researchers due to their superior properties, including nontoxicity, biocompatibility, low cost and facile synthesis, and high photoluminescence. In particular, doping heteroatoms with CDs can not only dramatically enhance the fluorescence but also greatly improve the electronic structure and doped CDs have been successfully applied in various technological fields. Herein, this minireview summarizes recent advances on the synthesis and optical properties of doped CDs and their promising applications for photocatalysis and electrocatalysis. Finally, some challenging issues as well as future perspectives of this exciting material are discussed.